Trocas gasosas, caracterização citogenética e vigor de sementes dos gêneros Opuntia e Nopalea. - Silva, Ronimeire Torres da (2019)
Widely cultivated in the Northeast Region of Brazil, forage palm belongs to the family Cactaceae, with Opuntia and Nopalea as the main genera. Studies involving gas exchange, chromosome variation and physiological quality of seeds belonging to different species in this family are still incipient. The objectives of this study were to evaluate the gas exchange, to correlate the ploidy levels with phenotypic characteristics of interest for genetic improvement and to analyze the physical and physiological quality of forage palm seeds as a function of ploidy level. The cultivars used were obtained at the Agronomic Institute of Pernambuco (IPA). The research was developed in three experiments: in the first (i), gas exchange evaluation was performed in 21 cultivars, belonging to Opuntia ficus-indica, O. stricta, O. undulata, O. atropes, Opuntia sp. and Nopalea cochenillifera. The cladodes were cultivated in a greenhouse, and the secondary cladode was evaluated at 00:00 hours, using the portable infrared gas analyzer - IRGA. Gas exchange parameters evaluated: CO2 net assimilation rate, stomatal conductance, CO2 concentration in intercellular space, transpiration and leaf temperature; Based in part on these data, the instantaneous and intrinsic water use efficiency and the instantaneous carboxylation efficiency were estimated. Data were statistically analyzed by boxplot and then subjected to multivariate principal component and cluster analysis. In the second experiment (ii), for chromosome characterization, six species of Opuntia, totaling 17 cultivars and 7 cultivars of N. cochenillifera were evaluated by double staining with the fluorochromes Chromomycin A3 (CMA) and 4′, 6-diamidino-2-phenylindole (DAPI). In the IPA Germplasm Bank, quantitative characteristics (width, length, thickness, cladode area, total number of cladodes, plant height and total photosynthetic area) were determined to be correlated with ploidy level; The degree of association between the ploidy level of each cultivar and the variables were analyzed using Pearson's linear correlation coefficient. The cultivars were separated into three groups based on the number of chromosomes: diploid (2n = 22), tetraploid (2n = 44) and octaploid (2n = 88). The evaluation of the productivity was done at the end of two year production cycle. The qualitative variables drought adaptation (1 = drought-adapted and 2 = less drought-adapted) and carmine cochineal resistance (A = resistant; B = susceptible), as well as the presence of thorns (few thorns = up to 4 thorns and many thorns = from 5 to 9 thorns per areolas) were characterized and evaluated by analysis of variance, and the Tukey test was applied to identify the source of significance. In the third experiment (iii), physical quality was characterized by mass of one thousand seeds and number of seeds per fruit and fruit biometrics taking into account: length, diameter and weight of fruits. For seed physiological quality analysis, the first emergence count, emergence percentage, seed electrical conductivity, shoot and root length, fresh and dry seedling mass were considered; The cladodes were analyzed by length, width, fresh and dry mass. Data analysis was performed in a nested scheme design, with three ploidy levels and three cultivars within each level. Based on the results of the first experiment, there was variation between genera and forage palm cultivars for gas exchange, being possible the formation of three cultivars groups and two main components. The cultivars ‘Verdura’ (Opuntia sp. _3) and ‘Orelha de Elefante Mexicana’ (O. stricta_1) have higher photosynthetic performance, while ‘IPA Clone 20’ (O. ficus-indica_3) and ‘F21 Sementes’ (Nopalea_1) have lower transpiration. The cultivars ‘Orelha de Elefante Mexicana’ (O. stricta_1); ‘Miúda’ (Nopalea_4) and ‘Copena’ (O. ficus-indica_1) have greater adaptation to arid and semiarid regions. In the second experiment, all cultivars of N. cochenillifera, O. atropes and O. undulata ‘Orelha de Elefante Africana’ have 2n = 22 chromosomes. Tetraploid individuals (2n = 44) were identified in four Opuntia and octaploid cultivars (2n = 88) in 10 cultivars of the same genus. CMA/DAPI banding revealed only one type of heterochromatin formed by CMA+/DAPI- bands. Regarding the third experiment, it was observed that the ploidy level is correlated positively (p < 0.05) with the number of seeds per fruit and the physiological quality of seeds and seedlings. However, cultivars behave differently (p < 0.05) within the same ploidy level. The vigor and emergence of polyploids stand out over diploids.